2021
DOI: 10.3389/fevo.2021.607338
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of Aeonium Species Across Macaronesian Archipelagos: Correlations Between Genome-Size Variation and Their Conservation Status

Abstract: The rich endemic flora of the Macaronesian Islands places these oceanic archipelagos among the top biodiversity hotspots worldwide. The radiations that have determined the evolution of many of these insular lineages resulted in a wealth of endemic species, many of which occur in a wide range of ecological niches, but show small distribution areas in each of them. Aeonium (Crassulaceae) is the most speciose lineage in the Canary Islands (ca. 40 taxa), and as such can be considered a good model system to underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, in angiosperms, large genomes were found to be maladaptive, and associated with extinction risk (Vinogradov, 2003) and rarity (Pandit et al, 2011). These broad patterns in plants were also reported at lower taxonomic levels, as in the Crassulaceae genus Aeonium (Brilhante et al, 2021). However, the relationship between angiosperm genome size and extinction risk has not been explicitly tested to date within a comprehensive evolutionary framework at a global scale, despite the considerable phylogenetic clustering of genome size across the angiosperm evolutionary tree (Carta et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in angiosperms, large genomes were found to be maladaptive, and associated with extinction risk (Vinogradov, 2003) and rarity (Pandit et al, 2011). These broad patterns in plants were also reported at lower taxonomic levels, as in the Crassulaceae genus Aeonium (Brilhante et al, 2021). However, the relationship between angiosperm genome size and extinction risk has not been explicitly tested to date within a comprehensive evolutionary framework at a global scale, despite the considerable phylogenetic clustering of genome size across the angiosperm evolutionary tree (Carta et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present a comparative study of genome size among the mainland populations incorporating environmental variables. The relationships between genome size and both bioclimatic and geographic variables have been widely studied among various groups of plants (Bottini et al, 2000 ; Brilhante et al, 2021 ; Díez et al, 2013 ; Suda et al, 2003 , 2005 ). Hitherto, during the various studies carried out, no universal consistency was reached between them.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the opposite trend was observed in the Crambe and Sonchus genera. Brilhante et al ( 2021 ) found negative correlations between annual mean precipitation and GS for Aeonium in Tenerife.…”
Section: Introductionmentioning
confidence: 99%
“…has the largest number of species (Bramwell & Bramwell, 2001;Acebes-Ginovés et al, 2010;Schönfelder & Schönfelder, 2018;BIOTA, 2021;Sauerbier et al, 2023) and has undoubtedly generated the largest number of natural hybrids in the entire archipelago, with about 80 known nothotaxa. Although hybrids of the genus Aeonium usually disappear from nature in the first filial generation, they can produce gene dilution in the pure species with which they coexist since pollen viability in some hybrids is 80-90% (Liu, 1989), which compromises their reproduction and makes them more vulnerable to various threats in the wild (Levin et al, 1996;Francisco-Ortega et al, 2000;Brilhante et al, 2021). Therefore, it is important to recognize them in nature, describe them, and deposit material well-preserved in the herbarium collections since these can contribute to understanding the phylogeny and evolution of this group of plants.…”
Section: Introductionmentioning
confidence: 99%